The Effects of Overeducation on Wages in Trinidad and Tobago: An Unconditional Quantile Regression Analysis - Roshnie Doon (Global Labor Organization (GLO), 2021)
The main aim of this study is to analyse the wage returns of Overeducated workers employed in Trinidad and Tobago. To undertake such a study, data from the Continuous Sample Survey of Population (CSSP) for the period 1991-2015 is used to estimate an initial OLS and Quantile regression version of the Mincerian Earnings equations, which is commonly used in the education mismatch literature. To observe the unconditional partial effects of small changes in wage returns of overeducated workers at the mean, the Recentred Influence Function is estimated. The results reveal that if the earnings of overeducated workers who receive low wages, was replaced with that of high wages, then this would lead to a rise, or shift in the returns of overeducated workers, if only their biographical information is considered. The inclusion of their skill and geographic location would cause their earnings to shift further. The shift in the earnings of overeducated workers, when examined across the wage distribution, would tend to favor those who were married, younger, i.e., in the 25-35 age group, who were highly skilled at their jobs. These groups of overeducated workers would experience the lowest wage penalties in comparison to their single, mature, and semi-skilled colleagues.
Keywords: D31; I26; J31; 330; Job-Education Mismatch; Overeducation; Unconditional Quantile Regression; Trinidad and Tobago